2019
DOI: 10.1016/j.cmet.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of β Cell Aging Determines Diabetes and Senolysis Improves Disease Outcomes

Abstract: Highlights d b cell senescence signature reveals loss of identity and upregulation of SASP factors d Insulin resistance accelerates the appearance of senescent b cells d Clearance of senescent cells improves glucose levels, b cell function, and identity d In humans, b cell senescence increases with type 2 diabetes, age, and BMI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
418
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(441 citation statements)
references
References 58 publications
20
418
1
2
Order By: Relevance
“…In addition to acquiring an oftentimes complex SASP, senescent cells can display a variety of biomarkers, including profound changes in heterochromatin (i.e., SADS) (27), DNA damage colocalized with telomeres (i.e., TAF) (28), and increased expression of the cyclin-dependent kinase inhibitors p16 Ink4a and p21 Cip1 (21). Accelerated accumulation of senescent cells has been identified in mice during obesity in adipose tissue, liver, and brain (13)(14)(15) and with T2D in the pancreas (e.g., senescent β cells) (16). In the latter study, HFD-induced obesity and insulin resistance in mice caused accelerated β cell senescence with a specific SASP, whereas senolysis (i.e., clearance of senescent cells) using either genetic or pharmacological approaches improved glucose homeostasis, β cell function, and the gene expression profile of β cells (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to acquiring an oftentimes complex SASP, senescent cells can display a variety of biomarkers, including profound changes in heterochromatin (i.e., SADS) (27), DNA damage colocalized with telomeres (i.e., TAF) (28), and increased expression of the cyclin-dependent kinase inhibitors p16 Ink4a and p21 Cip1 (21). Accelerated accumulation of senescent cells has been identified in mice during obesity in adipose tissue, liver, and brain (13)(14)(15) and with T2D in the pancreas (e.g., senescent β cells) (16). In the latter study, HFD-induced obesity and insulin resistance in mice caused accelerated β cell senescence with a specific SASP, whereas senolysis (i.e., clearance of senescent cells) using either genetic or pharmacological approaches improved glucose homeostasis, β cell function, and the gene expression profile of β cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified senescent cells in the bone microenvironment with aging (11) and found that targeting cellular senescence improved age-related bone loss (12). Furthermore, senescence has been shown to increase in adipose tissue, liver, and brain during obesity (13)(14)(15) and in pancreatic β cells, contributing to T2D (16). This led us to hypothesize that cellular senescence may be a mechanistic link between poor bone quality and T2D.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that insulin resistance accelerates β‐cell senescence and ageing in mice, leading to insulin secretory defects. Senolytic therapies, which specifically target senescent cells while sparing nonsenescent ones, improve the metabolic profile of different models of rodent insulin resistance and improve β‐cell function and gene expression profile …”
Section: Pathophysiology Of T2dmentioning
confidence: 99%
“…Senolytic therapies, which specifically target senescent cells while sparing nonsenescent ones, improve the metabolic profile of different models of rodent insulin resistance and improve β-cell function and gene expression profile. 83 Isolated β-cell function studies in the MA population are difficult to perform but are necessary to elucidate mechanisms behind the increased incidence and prevalence of T2D in this population.…”
Section: β-Cell Function and Senescencementioning
confidence: 99%
“…For example, it has been shown that β cells become senescent during the progression of Type I and Type II diabetes. Clearance of senescent β cells effectively restored β cell function and glucose homeostasis . Furthermore, ablation of senescent cells by transgenic clearance or treatment with senolytics improved pulmonary function and physical health in a murine model of idiopathic pulmonary fibrosis, a chronic respiratory disease the incident of which increases with aging .…”
Section: Organismal Aging and Cellular Senescencementioning
confidence: 58%